The function and Formation of NORTH ATLANTIC TREATY ORGANZIAITON as (NATO) Post Cold War Period (Journal of the College of Education for Women, 2018)
The problem of this study lies in that NATO was formed in the first place to protect Europe from Warsaw Pact. The geographical and military strategy have been changed with the change of its mission and expanding its operation scope with the leadership of the USA in the international scens. The latter has made this organization as the military arm to tighten its control over strategic regions. The research supposes that NATO state members confront security concerns and political and military issues that push to expand the organization. The importance of this study lies in knowing the new roles of NATO imposed by the United States. Therefore, the continuity and affirmation of NATO is a thing imposed by the satisfactions of the member states especially after the increase of military expenditures and the regional and international variables.